Effect of Plant Growth Regulators on Seed Yield of Mustard (Bangladesh Journal of Agricultural Research, 2023)
An experiment was conducted at the research field of Regional Agricultural Research Station (RARS), Bangladesh Agricultural Research Institute (BARI), Cumilla during November 2019 to March 2021 to find out the effect of two plant growth regulators (PGR) of IAA and GA3 on yield attributes and yield of mustard (Var. BARI Sarisha-17). There were seven treatments viz. T1= IAA 50 ppm, T2= IAA 75 ppm, T3= IAA 100 ppm, T4= GA3 50 ppm, T5= GA3 75 ppm, T6= GA3 100 ppm, and T7= Control. The PGRs was sprayed twice on mustard plant at 22 and 33 days after sowing. Plant height, branches plant-1, siliqua plant- 1, 1000 -seed weight and seed yield ha-1 were influenced significantly by different levels of application of plant growth regulators. The highest plant height (115.9 cm), branches plant-1 (6.2), siliqua plant-1 (79.8), 1000- seed weight (4.1) and seed yield (1788.3 kg ha-1) was obtained from T5 (GA3 - 75 ppm) treatment. The lowest seed yield was obtained from the control plants (T7). Application of GA3-50 ppm, GA3-100 ppm, IAA-100 ppm, IAA-75 ppm, IAA- 50 ppm gave statistical identical yield. The highest gross return (Tk. 89145 ha-1), gross margin (Tk. 53215 ha-1) and benefit cost ratio (2.47) were also obtained from GA3 at 75 ppm followed by GA3 at 50 ppm (2.43). Foliar application of GA3 and IAA at the rate of 75 ppm could be used at early growth stage for obtaining higher seed yield and economic return.Bangladesh J. Agril. Res. 47(1): 99-104, March 2022